2022
DOI: 10.1038/s41598-022-24220-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk of SARS-CoV-2 reinfection: a systematic review and meta-analysis

Abstract: This meta-analysis aims to synthesize global evidence on the risk of reinfection among people previously infected with SARS-CoV-2. We systematically searched PubMed, Scopus, Embase and Web of Science as of April 5, 2021. We conducted: (1) meta-analysis of cohort studies containing data sufficient for calculating the incidence rate of SARS-CoV-2 reinfection; (2) systematic review of case reports with confirmed SARS-CoV-2 reinfection cases. The reinfection incidence was pooled by zero-inflated beta distribution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 62 publications
1
21
0
1
Order By: Relevance
“…This study also indicated that the reinfection rate varies among different countries, such as Brazil, higher than other countries, with a reinfection rate of 6.60% (95% CI : 3.94 -10.84%), which migtht be influenced by different countries’ epidemic prevention policies, susceptible populations, ecological environment, etc. [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study also indicated that the reinfection rate varies among different countries, such as Brazil, higher than other countries, with a reinfection rate of 6.60% (95% CI : 3.94 -10.84%), which migtht be influenced by different countries’ epidemic prevention policies, susceptible populations, ecological environment, etc. [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The infectious individuals are further categorised as asymptomatic and symptomatic (mild and severe) according to their symptoms. Also, the recovered agents might become susceptible again due to the wanning effects of community 19 .
Figure 7 Flowchart of the transmission process of agent’s COVID health status.
…”
Section: Methodsmentioning
confidence: 99%
“…In addition, in this study, we select six major Long COVID symptoms discovered from the literature 19 and use the estimated ratios to simulate the sequela conditions in the case study. The ratios of recovered agents for getting respiratory conditions is 3.655%, diseases of the nervous system is 2.644%, mental health burden is 2.888%, metabolic disorders is 3.008%, poor general well-being is 3.705%, and cardiovascular conditions 4.864%.…”
Section: Methodsmentioning
confidence: 99%
“….It is also highly likely that the process of antigenic priming will begin to affect emerging variants following initial exposure to the Wuhan or subsequent strains. Acquired natural immunity (from any variant) has been shown to confer protection against the subsequent effects of further COVID-19 infection [103][104][105][106][107][108]. The extent of exposure to each variant is highly dependent on location as shown in Figures 7, A3.1 to A3.3.…”
Section: Roles For Immune Priming In Age Specificitymentioning
confidence: 99%